STUDI LITERATUR SISTEMATIS TENTANG KONSEP ASBAB AL-WURUD DALAM KAJIAN ILMU HADIS - Annisa Fitria Allicia Jauhar; Inka Puji Prastika (DIRAYAH : Jurnal Ilmu Hadis, 2025)
This study aims to systematically examine the literature discussing asbāb al-wurūd in the science of hadith, focusing on its urgency, role, methodology, and classification. Hadith studies cannot be separated from the socio-historical context in which they emerged. One of the key tools for understanding this context is asbāb al-wurūd, which refers to the causes or circumstances behind the emergence of a hadith. However, the use of Asbab al-Wurud in hadith literature remains limited. These limitations are evident in the lack of systematic development of Asbab al-Wurud in classical texts, the absence of robust methodological approaches in contemporary studies, and the suboptimal integration of asbāb al-wurūd in Islamic education curricula. As a result, contextual awareness in interpreting the full meaning of hadith remains underdeveloped. A Systematic Literature Review (SLR) was conducted using the PRISMA guidelines. Thematic analysis identified five main themes: first, the concept and urgency of asbāb al-wurūd, second, its role in resolving hadith contradictions, third, its application in tafsir and Islamic legal theory (Ushul Fiqh), fourth, the classification of asbab al-wurud (personal, social, and political), and fifth, critiques of textual approaches that neglect context. This study affirms that Asbab al-Wurud is not merely a complementary element, but a foundational component for understanding hadith in a contextual, applicable, and methodological manner. The findings recommend strengthening contextual approaches in hadith studies curricula and developing more integrative methodologies.